Review of ship behavior characteristics when operating at sea - SCURTU , Ionut Cristian; PRICOP, Mihail; TOMA, Alecu; ATODIRESEI, Dinu; POPESCU, Emil (Technium: Romanian Journal of Applied Sciences and Technology, 2022)
During activity 1.1. included in Platmarisc project authors collected information for initial evaluation for ship behavior characteristics when operating at sea. Identification of loads and their influence on the behavior of marine intervention platforms is one of the main contributions of the article. As first step in modelling of the 3D ship we will present the 3D initial Model in ModelMaker and the initial loading case according equipment loading onboard.